Trends and disparities in disease burden of age-related macular degeneration from 1990 to 2019: Results from the global burden of disease study 2019 - Bo Jiang; Chun Jiang; Jianqing Li; Peirong Lu (Frontiers Media S.A., 2023)
ObjectivesThis study aims to estimate the trends and disparities in the worldwide burden for health of AMD, overall and by age, sex, socio-demographic index (SDI), region, and nation using prevalence and years lived with disability (YLDs) from Global Burden of Disease (GBD) study 2019.MethodsThis retrospective study presents the prevalent AMD cases and YLDs from 1990-2019, as well as the age-standardized prevalence rate (ASPR) and age-standardized YLD rate (ASYR) of AMD. To measure changes over time, estimated annual percentage changes (EAPCs) of the age-standardized rates (ASRs) were analyzed globally, then studied further by sex, SDI, region, and nation. We included data from the 2019 Global Burden of Disease (GBD) database to examine AMD prevalence and YLDs from 1990-2019 in 204 countries and territories, as well as demographic information such as age, sex, SDI, region, and nation.ResultsGlobally, the number of prevalent AMD cases increased from 3,581,329.17 (95% uncertainty interval [UI], 3,025,619.4-4,188,835.7) in 1990 to 7,792,530 (95% UI, 6,526,081.5-9,159,394.9) in 2019, and the number of YLDs increased from 296,771.93 (95% uncertainty interval [UI], 205,462.8-418,699.82) in 1990 to 564,055.1 (95% UI, 392,930.7-789,194.64) in 2019. The ASPR of AMD had a decreased trend with an EAPC of −0.15 (95% confidence interval [CI], −0.2 to −0.11) from 1990 to 2019, and the ASYR of AMD showed a decreased trend with an EAPC of −0.71 (95% confidence interval [CI], −0.78 to −0.65) during this period. The prevalence and YLDs of AMD in adults over 50 years of age showed a significant increase. The prevalence and YLDs of AMD were significantly higher in females than males, overall. The ASPRs and ASYRs in low SDI regions was greater than in high SDI regions from 1990 to 2019. In addition, increases in prevalence and YLDs differed by regions and nations, as well as level of socio-economic development.ConclusionThe number of prevalent cases and YLDs due to AMD increased over 30 years and were directly linked to age, sex, socio-economic status, and geographic location. These findings can not only guide public health work but also provide an epidemiological basis for global strategy formulation regarding this global health challenge.